Knowledge Regarding Modifiable Risk Factors about Coronary Artery Disease in an Urban Male Population (Medical Forum Monthly, 2024)
Objective: To ascertain knowledge of modifiable risk factors about coronary artery disease in an urban male population of Sargodha city; Pakistan.Study Design: Observational / cross sectional study.Place and Duration of Study: This study was carried in urban male population of Sargodha city, Pakistan from November, 1st to 30th 2015.Materials and Methods: This study was carried out to recognize knowledge of modifiable risk factors about coronary artery disease in an urban male population of Sargodha city. All 100 married male apparently healthy participants; 25-60 years of age were included.Results: The mean age of subjects was 40.12±10.22 years. The frequency of smoking (28%) was significantly higher in study population, sedentary lifestyle (25%) obesity (22%), use of salt (17%) and use of fat (8%) respectively.Conclusion: The present study determines a poor knowledge of modifiable risk factors regarding Coronary artery disease in the urban male population. Therefore, there is an immediate need to initiate measures to raise awareness of these modifiable risk factors so that individuals at high risk for future Coronary artery disease can be managed.